2017
DOI: 10.18632/oncotarget.21569
|View full text |Cite
|
Sign up to set email alerts
|

Expression of protein disulfide isomerase family members correlates with tumor progression and patient survival in ovarian cancer

Abstract: ObjectiveProtein disulfide isomerase (PDI) is an oxidoreductase that is overexpressed in several cancers. PDI family members (PDIs) play a role in various diseases including cancer. Select PDIs were reported as useful markers in other cancers but their expression in ovarian cancer has not been thoroughly assessed. We sought to evaluate the expression of PDI, PDIA6, PDIR, ERp57, ERp72 and AGR3 in ovarian cancer patient samples and examine their prognostic significance.MethodsTMA samples from 415 tissues collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…The Kaplan-Meier survival analysis method was used to generate survival curves using low (<median expression) and high expression (>median expression) groups. For the PDI survival curve, part of the data was used in previously published article 25 . (2020) 10:2160 | https://doi.org/10.1038/s41598-020-59116-x www.nature.com/scientificreports www.nature.com/scientificreports/ showed prognostic value in cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Kaplan-Meier survival analysis method was used to generate survival curves using low (<median expression) and high expression (>median expression) groups. For the PDI survival curve, part of the data was used in previously published article 25 . (2020) 10:2160 | https://doi.org/10.1038/s41598-020-59116-x www.nature.com/scientificreports www.nature.com/scientificreports/ showed prognostic value in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry and automated analysis of immunohistochemistry. Immunohistochemical (IHC) staining was performed by the Pathology Core at the University of Michigan as previously described 25 . Briefly, IHC staining was used to assess protein expression on TMA slides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we evaluated the expression pro le of PDIA6 in OSCC tissues using qPCR and western blotting assays, and found that PDIA6 expression level was apparently increased in OSCC tissues. PDIA6 expression pattern in OSCC was consistent with NSCLC (15), bladder cancer (16), ovarian cancer (21) and hepatocellular carcinoma (17). Further analysis showed that higher level of PDIA6 in OSCC patients was closely associated with lower overall survival, higher TNM stage (p = 0.006), poorer tissue differentiation (p = 0.036) and perineural invasion (p = 0.034).…”
Section: Discussionmentioning
confidence: 54%
“…The ectopic expression and function of PDIA4 had also been reported in ovarian cancer. In ovarian carcinoma, PDIA4 was found to take part in the drug-resistance phenotype and can serve as a critical prognostic marker [19,20]. Moreover, in pancreatic carcinoma, hepatocellular carcinoma and esophageal squamous cell carcinoma, the increased expression of PDIA4 was respectively observed and associated with tumor development [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%